Prediction of Mechanical Properties of Glass Fiber Reinforced Concrete Using Micromechanical Techniques - Kavya B R; H S Sureshchandra; Shrikanth A S (International Journal of Sustainable Construction Engineering and Technology, 2025)
A composite material is a combination of two or more materials on a macroscopic scale whose mechanical properties depend on the volume percentage and characteristics of their primary constituents. Concrete is the most common man-made composite in the world used for construction purposes. Determining the important mechanical properties of the concrete and selecting the best combination of the constituents is a major task in the construction industry. This paper is based on homogenization theory and finite element modeling to predict the Young’s modulus, shear modulus and Poisson ratio of glass fiber reinforced concrete. In order to determine the above properties of fiber reinforced concrete, the elastic tensor matrix of a unidirectionally distributed fiber reinforced concrete composite was solved using the Voigt and Ruess series model. Furthermore, Abaqus was used to simulate the axial compression of fiber-reinforced concrete, yielding the desired results. The accuracy was confirmed by a comparison between the theoretically anticipated values based on homogenization and the simulated values from the finite element method.